Usage of Discriminant Models in Bankruptcy Prediction - Karolina RYBICKA (Communications of International Proceedings, 2023)
The financial situation is an important issue for company managers. An enterprise's financial problems may threaten its insolvency; therefore, an analysis of the financial situation is necessary not only for ongoing management, but also helps protect against the negative effects of the economic downturn. Warning signals spotted early enough, and decisions made based on them can prevent company bankruptcy. For many years, attempts have been made to develop measures that will allow managers to be warned in time about threats to financial security and, above all, to identify the causes of this threat. The issue of company bankruptcy is the subject of numerous studies and scientific research, which address both the issue of bankruptcy determinants and their application in assessing the condition of the company. There are many methods of bankruptcy prediction in scientific literature and business practice. The purpose of the paper is to select the best discriminant models that can indicate the worsening situation of an enterprise. The most famous model is introduced by Altman, but there are also many other approaches to prediction models of potential bankruptcy. This paper is based on the literature study (both Polish and foreign authors) and analysis of financial ratios in examined company. For purpose of this analysis the author considers chosen models of prediction, mostly of Polish scientists, because of more tight connection with the reality of examined Polish companies. There is presented appraisal of the risk of bankruptcy of the company from pharmaceutical industry. Analyzed company has rather good financial condition and at this moment it is not financial danger of bankruptcy.
Keywords: bankruptcy; prediction; discriminant analysis models